Distance-Aware Beamforming for Multiuser Secure Communication Systems - Nasrin Ravansalar; Vahid Pourahmadi (AUT Journal of Electrical Engineering, 2020)
Typical cryptography schemes are not well suited for low complexity types of equipment, e.g., Internet of things (IoT) devices, as they may need high power or impose high computational complexity on the device. Physical (PHY) layer security techniques such as beamforming (in multiple antennas systems)  are possible alternatives to provide security for such applications. In this paper, we consider a network with multiple groups of users as receivers and a transmitter that intends to send different messages to each group of users. There are also some eavesdroppers (Eavs) at known locations of the environment. The goal of this paper is to find the beamforming vectors that minimize the total transmitting power while keeping the signal level above a threshold at the exact locations of the legitimate receivers (both angle and range) and keeping it less than another threshold at eavesdropping points.  We use frequency diverse arrays (FDA) at the transmitter; thus, the transmitter also needs to determine the frequency that each antenna element must use for data transmission. This condition makes the problem non-convex and so we propose an approximate solution for solving this optimization problem. Simulation results show the performance of the proposed scheme in a particular network setting.